The antioxidant and hepatoprotective activities of two tea polysaccharides - Shi, Yutao; Aia, Yujie; Chena, Yuqiong; Ni, Dejiang; Yu, Zhi (Journal of Antioxidant Activity, 2017)
In the present study, we investigated the chemical compositions, in vitro antioxidant and in vivo hepatoprotective activities of two tea polysaccharides (TPS), which were extracted from two different tea cultivars, Yingshuang (Camellia Senesis, T01) and Yunnan Dayezhong (Camellia Senesis, T09). Compared with T09-TPS, T01-TPS had lower contents of neutral sugar, protein, uronic acid and polyphenol. However, T01-TPS showed stronger scavenging abilities for transient free radicals of hydroxyl radical and superoxide anion radicals and lipid peroxidation inhibition effect, but weaker scavenging ability for stable free radical of DPPH. For hepatoprotective activity in vivo, the results demonstrated that both T01-TPS and T09-TPS could significantly prevent the increase of serum alanine aminotransferase and, aspartate aminotransferase levels, decrease the liver index, reduce the formation of malonydialdehyde and enhance the activities of superoxide dismutase, glutathione peroxidase and peroxidase in carbon tetrachloride-induced liver injury mice. These results suggest that T01-TPS and T09-TPS have potent antioxidant and hepatoprotective activities.
Keywords: Tea polysaccharides; Antioxidant activity; Hepatoprotective activity